1962
DOI: 10.1002/path.1700830212
|View full text |Cite
|
Sign up to set email alerts
|

A histochemical study of long bones in osteogenesis imperfecta congenita

Abstract: Stewart, Robert B. (University of Rochester, Rochester, N. Y.). Growth and lethal effects of the psittacosis agent in chicken embryos of different ages. J. Bacteriol. 83:423-428. 1962.-Inoculation of the psittacosis agent (strain 6BC) into the yolk sacs of chicken eggs in different stages of embryonic development resulted in a steady decrease in ld(50) titer as the embryos increased in age from 7 to 10 days. Correlated with the decreased ld(50) titers in older eggs was the finding that the titers of the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1963
1963
1996
1996

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…structural observations suggest either a defect of the bone matrix involving collagen [25] or a functional impairment of osteoblastic activity [6]. In 1962 Spencer [24] had histochemical evidence for the presence of abnormally staining proteoglycans in long bones of one case of osteogenesis imperfecta with multiple fractures at birthprobably lethal perinatal 01. Furthermore, Solheini in 1969 [21], extracted over-sulfated chondroitin sulfates from long bones of one case of osteogenesis imperfecta "tarda."…”
Section: Ntr Oductjonmentioning
confidence: 99%
“…structural observations suggest either a defect of the bone matrix involving collagen [25] or a functional impairment of osteoblastic activity [6]. In 1962 Spencer [24] had histochemical evidence for the presence of abnormally staining proteoglycans in long bones of one case of osteogenesis imperfecta with multiple fractures at birthprobably lethal perinatal 01. Furthermore, Solheini in 1969 [21], extracted over-sulfated chondroitin sulfates from long bones of one case of osteogenesis imperfecta "tarda."…”
Section: Ntr Oductjonmentioning
confidence: 99%
“…Several other authors have reported alterations in glycosaminoglycans in 01 (Spencer, 1962;Solheim, 1969;Bleckmann et al, 1971;Engfeldt & Hjerpe, 1976;Cetta et al, 1977). An increase in the total amounts of glycosaminoglycans in OI bone and cartilage (Spencer, 1962;Bleckmann et al, 1971) and in their sulphation (Engfeldt & Hjerpe, 1976) has been reported. However, a low chondroitin sulphate content has been recorded in some bone and cartilage specimens (Solheim, 1969;Cetta et al, 1977).…”
Section: Discussionmentioning
confidence: 93%
“…There is evidence that an increase in acid mucopolysaccharide may inhibit the crystal nucleation process of ossification (Neuman, 1960;Spencer, 1962).…”
Section: Discussionmentioning
confidence: 99%